2012
DOI: 10.1001/archophthalmol.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Retinal Detachment After Phacoemulsification

Abstract: Risk for RD after phacoemulsification has almost halved for each 5-year period since its adoption in the mid 1980s. Younger patient age and male sex at surgery significantly increased risk for RD. Phacoemulsification requiring anterior vitrectomy vastly increased risk for RD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 42 publications
(95 reference statements)
2
28
1
Order By: Relevance
“…Male gender is a well established risk factor considered to increase the RD rate by 2.5-fold 2 3. In our study, the respective HR was 2.0 (95% CI 1.03 to 3.88) and was significant in the univariate model (p=0.04) but not in the multivariate model (p=0.43).…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Male gender is a well established risk factor considered to increase the RD rate by 2.5-fold 2 3. In our study, the respective HR was 2.0 (95% CI 1.03 to 3.88) and was significant in the univariate model (p=0.04) but not in the multivariate model (p=0.43).…”
Section: Discussionmentioning
confidence: 46%
“…The rate of RD in our study may also reflect a truly reduced incidence of RD in the phacoemulsification compared with extracapsular cataract extraction (ECCE) era. Clark et al 2 in a study of 65 055 eyes operated between 1989 and 2001 reported a 10-year RD rate of 0.68%, but when comparing consecutive time periods he found a significant drop in RD rates from 0.96% between 1989 and 1993 to 0.25% for those operated between 1999 and 2001. Lin et al 5 reported a 7-year cumulative RD rate of 0.84% in 9184 eyes having cataract surgery from 2000 to 2010, but this study included ECCE and the female:male ratio was 1:2.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations